2023
DOI: 10.1038/s41598-022-27152-4
|View full text |Cite
|
Sign up to set email alerts
|

Adult skin fibroblast state change in murine wound healing

Abstract: Wound healing is a well-organized dynamic process involving coordinated consecutive phases: homeostasis, inflammation, proliferation and resolution. Fibroblasts play major roles in skin wound healing such as in wound contraction and release of growth factors which are of importance in angiogenesis and tissue remodeling. Abnormal fibroblast phenotypes have been identified in patients with chronic wounds. In this work, we analyzed scRNA-seq datasets of normal and wounded skin from mice at day 4 post-wound to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Moreover, it is a constitutive component of the interleukin‐3 receptor complex, is involved in neutrophil and platelet activation and may function cooperatively with other activating receptors. Interestingly, FCER1G was among the top up‐regulated genes involved in granulocyte chemotaxis in wounded mouse skin (Gharbia et al, 2023). Additionally, studies have demonstrated that ITAM‐containing Fc receptor common gamma subunits are required for the maintenance of bone homeostasis through activating signals for osteoclastogenesis in mice (Koga et al, 2004) and that FcεRI‐mediated activation in transfected rat basophil leukaemia cells is inhibited by SIGLEC5 (Avril et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is a constitutive component of the interleukin‐3 receptor complex, is involved in neutrophil and platelet activation and may function cooperatively with other activating receptors. Interestingly, FCER1G was among the top up‐regulated genes involved in granulocyte chemotaxis in wounded mouse skin (Gharbia et al, 2023). Additionally, studies have demonstrated that ITAM‐containing Fc receptor common gamma subunits are required for the maintenance of bone homeostasis through activating signals for osteoclastogenesis in mice (Koga et al, 2004) and that FcεRI‐mediated activation in transfected rat basophil leukaemia cells is inhibited by SIGLEC5 (Avril et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that SFRP2 and TGF have similar effects on fibroblasts suggests that SFRP2 affects the mesenchymal status of the cells. A previous study on wound healing demonstrated that fibroblasts are predominant in the wound during the proliferation stage [ 36 ]. Importantly, this study showed that fibroblasts have the highest gene expression of EMT markers while concomitantly, SFRP2 is one of the most upregulated plasma membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast proliferation is critical for filling the tissue space formed after injury with proliferating fibroblasts and synthesizing the ECM, which is destroyed by an increase in the number of fibroblasts in the wound area [73][74][75][76] . TNF-α levels in circulating plasma are generally around 11 pg/mL while in healthy skin tissue TNF-α levels are about 1.5 ng/mL 77,78 .…”
Section: Fibroproliferative Effects Of L-eps Produced From L Plantaru...mentioning
confidence: 99%